2014
DOI: 10.1111/cns.12228
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of Seizure‐like Events by Hydrogen Sulfide: Involvement of Multiple Targets that Control Neuronal Excitability

Abstract: These results suggest a pathological role of increased H2 S level in SLEs in vivo and in vitro. Enzymes that control H2 S biosynthesis could be interesting targets for antiepileptic strategies in poststroke epilepsy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 44 publications
3
27
3
Order By: Relevance
“…H 2 S mediates ischemic damage pursuant to stroke in neuronal tissue (15), whereas it serves as a powerful cardioprotective agent upon comparable conditions. One categorical correlation that emerged in the studies highlighting this 'dual physiological effect' by the gaseous mediator is that while H 2 S depolarizes cerebral components (8)(9)(10)(11)(12), it hyperpolarizes cardiomyocytes (13,14). In other words, H 2 S increases the excitability of cerebral tissue, worsening seizure-like symptoms and rendering neurons more susceptible to ischemic insult (12,15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…H 2 S mediates ischemic damage pursuant to stroke in neuronal tissue (15), whereas it serves as a powerful cardioprotective agent upon comparable conditions. One categorical correlation that emerged in the studies highlighting this 'dual physiological effect' by the gaseous mediator is that while H 2 S depolarizes cerebral components (8)(9)(10)(11)(12), it hyperpolarizes cardiomyocytes (13,14). In other words, H 2 S increases the excitability of cerebral tissue, worsening seizure-like symptoms and rendering neurons more susceptible to ischemic insult (12,15).…”
Section: Discussionmentioning
confidence: 99%
“…One categorical correlation that emerged in the studies highlighting this 'dual physiological effect' by the gaseous mediator is that while H 2 S depolarizes cerebral components (8)(9)(10)(11)(12), it hyperpolarizes cardiomyocytes (13,14). In other words, H 2 S increases the excitability of cerebral tissue, worsening seizure-like symptoms and rendering neurons more susceptible to ischemic insult (12,15). In contrast, H 2 S depresses the excitability of the heart, in which H 2 S is cardioprotective in ischemia and reperfusion (I/R) injury models when administered either through a pre-I/R (16,18,19) or post-I/R (20) treatment regime.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also shown that H 2 S can increase neuronal excitability in rat trigedeminal ganglion neurons [27] and rat epileptic seizure models [28] . In addition, an increase in the plasma level of H 2 S was found in a febrile seizure rat model [29] .…”
Section: Discussionmentioning
confidence: 85%